Wisata Halal Sebuah Strategi untuk Memaksimalkan Penyerapan Tenaga Kerja di Provinsi Lampung - Siatan, Mairizal Salehudin (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes that it is hoped that this country would be able to create many jobs in order to have strong economic growth. The goal of this study is to give the findings of an investigation of the impact of economic expansion on labor absorption in the province of Lampung. In order to address the labor issues in Lampung Province, analysis will be used to seek for correlations between variables, underlying causes, and potential policy solutions. Based on the results of the analysis, it can be concluded that the absorption of labor in Lampung Province is influenced by GRDP/share of tourism sector, Total Population Completed High School, and percentage change in room occupancy rate. GRDP/share of tourism sector has a significant relationship between the number of working people. The number of people who work has a significant relationship to the number of residents who have a positive relationship to the number of people who work with the last education graduated from high school.  Tourism is believed to be a solution to the low employment absorption in Lampung province. The development of halal tourism besides being able to increase economic growth will also be able to spur maximum employment absorption. Based on the R square value of 0.995, it is revealed if there is a good enough influence on the independent variable on the dependent variable as shown by the total working population of 99.5 percent, while the remaining 0.5 percent reveals that there are other facts